(untitled) (Orfeu, 2017)
The present article aims to contribute to reflections regarding different processes of preparation for free musical improvisation, with aid of the idea of “care of the self”, as presented by Michel Foucault in the Hermeneutics of the Subject. The philosopher conducts a study of this concept and associated practices, among classic Greek philosophers and follows it to the time of Descartes when it is dissociated from “know thyself”. By way of revision of Foucault’s work, we shall attempt to describe concepts which may aid us in looking at practices of preparation for free musical improvisation. As reference for studies in the field of learning musical improvisation, we shall present ideas from researches which bring together music and cognitive sciences. Lastly we shall offer our reflection based on the practices studied herein, and we shall search for tools for the comprehension of the preparation for free musical improvisation, which contemplate more than the motor rehearsal of the actions of the performance.